Virtual Reality Application of Traditional Malay House: Bringing Tourists into 3-Dimensional Virtual World - Muhammad Abdul Malik, Saedon (2010)
The focus of this research is to conduct a survey questionnaire among local and foreign tourists to collect data towards virtual reality technology of traditional Malay house for the promotion. The existing application of traditional Malay house developed based on virtual reality (VR) technology and in the field of virtual heritage. In this field, the heritage of a traditional Malay house will be presented among local and foreign tourists. The purpose of this application is to promote the traditional Malay house as well as the Malay heritage to the tourists. An evaluation on the acceptance and usability of the application among them will be measure. This will determine their responses towards the utilization of VR technology in promoting these areas. At the end of this research, a conclusion on the potential use of VR technology in promoting the traditional Malay house as well as the Malay heritage in the tourism sector could be made.